2019
DOI: 10.1186/s13046-019-1088-0
|View full text |Cite
|
Sign up to set email alerts
|

LRG-1 promotes pancreatic cancer growth and metastasis via modulation of the EGFR/p38 signaling

Abstract: Background The abnormal expression of leucine-rich-alpha-2-glycoprotein 1 (LRG-1) is reported to be associated with multiple malignancies, but its role in the progression of pancreatic ductal adenocarcinoma (PDAC) remains to be determined. Methods The expression of LRG-1 was assessed in PDAC tissues by RT-PCR, Western blot and immunohistochemistry. LRG-1-silenced or overexpressed cell lines were constructed using shRNA or LRG-1-overexpressing plasmids. EdU incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…We also demonstrated a promoting role of LRG1 in the expression of cell-cycle marker cyclin D1. These results are in line with previous studies that LRG1 increases proliferation of different epithelial-derived cancer cells, such as colorectal cancer cells ( 40 ), pancreatic ductal adenocarcinoma ( 17 ), non-small-cell lung cancer cells ( 41 ), and gastric cancer cells ( 15 ). Consistent with the previous report ( 21 ), we showed that LRG1 overexpression and knockdown affect keratinocyte migration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also demonstrated a promoting role of LRG1 in the expression of cell-cycle marker cyclin D1. These results are in line with previous studies that LRG1 increases proliferation of different epithelial-derived cancer cells, such as colorectal cancer cells ( 40 ), pancreatic ductal adenocarcinoma ( 17 ), non-small-cell lung cancer cells ( 41 ), and gastric cancer cells ( 15 ). Consistent with the previous report ( 21 ), we showed that LRG1 overexpression and knockdown affect keratinocyte migration.…”
Section: Discussionsupporting
confidence: 93%
“…Leucine-rich α-2-glycoprotein 1 (LRG1) is a secreted glycoprotein that was previously reported to regulate pathological neovascularization in the eye by switching the angiostatic TGFβ1-Smad2/3 signaling toward the proangiogenic TGFβ1-Smad1/5/8 signaling in endothelial cells ( 11 ). Besides its role in ocular angiogenesis, LRG1 is intimately associated with many inflammatory and autoimmune conditions ( 12 14 ) and tumor malignancy ( 15 17 ), which shares fundamental molecular mechanisms with chronic wound healing ( 18 ). Recently, elevated serum LRG1 levels were reported in patients with diabetes with peripheral arterial disease ( 19 ), a major risk factor for diabetic foot ulcers (DFU) ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…When EGFR triggers by growth factors, it mainly regulates cell proliferation and other biological processes through activation of downstream signaling pathways [ 20 ]. EGFR activation-associated downstream signaling pathway mainly includes ERK [ 21 ], p38 [ 22 ] and AKT [ 23 ] signaling pathways, which have to explore on the potential functional mechanism by which Eppk1 mediates cell proliferation of CC. Besides, KLF5 widely expresses in different tissues and plays a higher role in cell proliferation than in cell differentiation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR activation-associated downstream signaling pathway mainly includes ERK [21], p38 [22] and AKT [23] signalings, which need to explored the potential functional mechanism by which Eppk1 mediates cell proliferation of CC. Furthermore, KLF5 is widely expressed in different tissues and plays a higher role in cell proliferation than in cell differentiation [24].…”
Section: Discussionmentioning
confidence: 99%